Physiology Question-Based Learning : Cardio, Respiratory and Renal Systems - Cheng, Hwee Ming (Springer International Publishing : Imprint: Springer, 2015)
This work provides the reader with various sets of questions and answers related to basic human physiology. The questions are formulated to test concepts and assess the thinking process in physiology and to discover any misperceptions in the current knowledge of physiology. Readers will find that this book has been split into three main themes; cardiovascular, respiratory and renal physiology. The homeostatic mechanisms within each system will be covered. In addition, the functional integration of the physiology of these three organ systems will also be considered. The author of this physiology question-based learning book has taught physiology for more than twenty five years. He is also the pioneer of the physiology quiz, which he facilitates as quiz master, for which he generates the challenging physiology questions. This book is a distillation of the questions asked at the international editions of the physiology quiz. This physiology question-based learning book will be useful to all students of physiology in medicine, dentistry, pharmacy and other allied health sciences. This question-based learning text aims to provoke thinking and it should make learning physiology both enjoyable and challenging.